Variation of resistance to axial compression of the Portland cement concrete with addition of detergent as additive air incorporator (Research, Society and Development, 2019)
The simple concrete, obtained material from the mixture of cement, aggregates (sand and gravel) and water, can be considered today as the most used construction material. Seeking to further improve the mechanical characteristics of the concrete; resistance to compression, abrasion resistance, permeability, proper weight and even curing time, various materials and additives have been added to the blend. In order to analyze the physical and mechanical characteristics of Portland cement concrete, by adding detergent as an air-entraining additive, this research was started. For this, weighed and axial compression tests were carried out on molded test pieces with three different traces, one of them without addition of detergent and two of them with addition of detergent in the percentages of 0.125% and 0.250% in relation to the quantity of cement determined for the mixture. Through the tests carried out, the weight and resistance decrease was observed in an exponential way, thus, the higher the percentage of detergent, in relation to the cement, the greater reduction of weight and resistance. A reduction in the amount of water required for mixing has also been noted to ensure good consistency and workability.